1, 3-Phenylene-bridged naphthalene wheels synthesized by one-pot Suzuki–Miyaura coupling and the complex of the hexamer with C60. Issue 37 (7th June 2018) - Mei, Peifeng; Matsumoto, Akinobu; Hayashi, Hironobu; Suzuki, Mitsuharu; Aratani, Naoki; Yamada, Hiroko
Abstract : 1, 3-Phenylene-bridged cyclic hexa-naphthalene synthesized by Suzuki–Miyaura coupling via a one-pot reaction formed a co-crystal with C60 to exhibit a 1D alignment of fullerene. Abstract : A large 1, 3-phenylene-bridged hexameric naphthalene wheelN6 and a heptameric wheelN7 were synthesized simply by Suzuki–Miyaura coupling via one-pot reaction from monomers. We could control the distribution ofN6 andN7 via the reaction conditions. The hexameric wheel structure was revealed by X-ray diffraction analysis. The wheelN6 exhibited C60 encapsulation ability in the solid state, which was also confirmed by single crystal X-ray analysis.